Identification of the Microbiota in Coconut Water, Kefir, Coconut Water Kefir and Coconut Water Kefir-Fermented Sourdough Using Culture-Dependent Techniques and Illumina–MiSeq Sequencing - Limbad, Mansi; Gutierrez Maddox, Noemi; Hamid, Nazimah; Kantono, Kevin; Higgins, Colleen (MDPI AG, 2024)
The principal objective of this study was to isolate and identify the microorganisms present in commercial kefir grains, a novel kefir-fermented coconut water (CWK) and a novel coconut water kefir-fermented sourdough using phenotypic identification and Sanger sequencing and examine the microbial diversity of CWK and CWK-fermented sourdough throughout the fermentation process using the MiSeq Illumina sequencing method. The phenotypic characterisation based on morphology identified ten isolates of LAB, five AAB and seven yeasts from kefir (K), CWK and CWK-fermented sourdough (CWKS). The results confirm the presence of the LAB species Limosilactobacillus fermentum, Lactobacillus. plantarum, L. fusant, L. reuteri and L. kunkeei; the AAB species Acetobacter aceti, A. lovaniensis and A. pasteurianus; and the yeast species Candida kefyr, Rhodotorula mucilaginosa, Saccharomyces cerevisiae, C. guilliermondii and C. colliculosa. To the best of our knowledge, the identification of Rhodotorula from kefir is being reported for the first time. This study provides important insights into the relative abundances of the microorganisms in CWKS. A decrease in pH and an increase in the titratable acidity for CWK- and CWK-fermented sourdough corresponded to the increase in D- and L-lactic acid production after 96 h of fermentation. Significant reductions in the pHs of CWK and CWKS were observed between 48 and 96 h of fermentation, indicating that the kefir microorganisms were able to sustain highly acidic environments. There was also increased production of L-lactic acid with fermentation, which was almost twice that of D-lactic acid in CWK.
Keywords: 3107 Microbiology; 31 Biological Sciences; 3106 Industrial Biotechnology; 3107 Microbiology; 3207 Medical microbiology